2005
DOI: 10.2220/biomedres.26.279
|View full text |Cite
|
Sign up to set email alerts
|

Structure and component alteration of rabbit Achilles tendon in tissue culture

Abstract: The aim of this study was to investigate alterations of cultured tendon tissues to determine whether tissue culture is a useful method for biological analyses of the tendon. Tendon tissues for tissue culture were isolated from Achilles tendons of rabbits. The tendon segments were placed one segment per well and incubated in growth medium consisting of Dullbecco's modified Eagle's medium supplemented with 5% fetal bovine serum at 37°C in a humidified atmosphere with 5% CO 2 for various periods. The alignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…TNFα is produced by various cells and enhances many biological events, including production of MMPs and stimulation or inhibition of cellular proliferation, and secreted TNFα stimulates cells to synthesize IL-1β in a para/autocrine manner (12,27,28). Even in the tendon, these gelatinases and pro-infl ammatory cytokines are synthesized by tendinocytes and are involved in the turnover of tendon tissue and in the maintenance of homeostasis (9,15,16,23). In several types of fi broblast-like cells, pro-infl ammatory cytokines can activate both MMP-2 and -9 (45).…”
Section: Figmentioning
confidence: 99%
“…TNFα is produced by various cells and enhances many biological events, including production of MMPs and stimulation or inhibition of cellular proliferation, and secreted TNFα stimulates cells to synthesize IL-1β in a para/autocrine manner (12,27,28). Even in the tendon, these gelatinases and pro-infl ammatory cytokines are synthesized by tendinocytes and are involved in the turnover of tendon tissue and in the maintenance of homeostasis (9,15,16,23). In several types of fi broblast-like cells, pro-infl ammatory cytokines can activate both MMP-2 and -9 (45).…”
Section: Figmentioning
confidence: 99%
“…The tumor necrosis factor receptor superfamily (TNFRSF) is an ancient family of molecules which is present in both vertebrates (Su et al, 1992; Tan et al, 1997; Bridgham et al, 2001; Bridgham and Johnson, 2003; Tamura et al, 2004; Hosaka et al, 2005; Iha et al, 2009) and invertebrates (Ouwe-Missi-Oukem-Boyer et al, 1994; Kauppila et al, 2003; Wang et al, 2006; Kato et al, 2009; Li et al, 2009). For many years, the focus on the immunological and pathological role of TNFRSF members and their ligands (the TNFSF or tumor necrosis factor superfamily) has overshadowed research examining non-immunological functions for these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This was associated with histological evidence of collagen degradation. Other studies have reported an increase in MMP2 (Hosaka et al, 2005), MMP9 (Hosaka et al, 2005; Jones et al, 2006), and MMP13 (Nomura et al, 2007) expression in models of chronic tendonitis.…”
Section: Discussionmentioning
confidence: 85%